(untitled) (European Journal of Marketing and Economics, 2024)
C19, the pension system has an important role in developing countries’ economies. It is very important in the context of the social security. During the last two decades, pension plan in Albania, has passed important transformation in all aspects. So the first goal is maintaining the stability of this system. The aim of this paper is to analyze the efficiency and sustainability of the existing pension system in the Albania and the identification of key factors, which determine its further stability. We should point out that life insurance market and pension plan in Albania are noticeably underdeveloped compared to other European countries, but in the recent years it has been developing moderately under the influence of various factors. Many economic factors have an impact on it, and some of them are globalization, global economic crisis and expressed instability of financial markets. Other factors like demographic factors: mortality rate, life expectancy and net migration have also impact on retirement risk, but in this paper we will analyze and indicate the most significant economic and demographic factors.